UPAYA MENINGKATKAN MINAT DAN PRESTASI BELAJAR MATEMATIKA SISWA DENGAN MENGGUNAKAN PENERAPAN PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF - Maria Theresia Hery (Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun, 2015)
Mathematic Lesson that runs monotonously during this time and make students tends to be bored and it becomes something terrifying for students. Enjoyable mathematic lesson does not only help students to enjoy Mathematic but also increase achievement of student’s lesson. Great development in technology lately if it is used well in Mathematic education can help teacher to develop interesting and innovative lesson material for lesson process of Mathematic. One of technology application that can be used is creating lesson material for interactive multimedia. By this interactive multimedia lesson material, students are helped optimally to understand material of lesson step by step. This method also makes students to be challenged to follow some exercises or quiz. Direct interaction that runs maximally can make students understand carefully of material lesson that is being discussed. The aim of this research is to increase interest and achievement of students’ lesson mathematic by using application of lesson based on interactive multimedia. This kind of research is the class action research that is done two cycles. This research is done in SMP Negeri 6 Madiun. Subject of this research is students in seventh grade in a class 20011/2012 with 27 students. The object of this research is application of interactive multimedia in mathematic lesson. The result of steps that is done in this research is: Achievement of students’ Mathematic study increases from cycle I, 4% become 52.17% in cycle II. The interest of students’ Mathematic study decreases. Percentage of the interest students’ Mathematic study before this research was done is on high category 77% and on medium category 23%, in the cycle I, the interest of students’ Mathematic study in the high category 69% and in the medium category 31%, and in the cycle II high category 69% and medium cycle 37%. The result of management observation lesson increases from cycle I 3.485 becomes 3.520 in cycle II and all of them in a good category.